Facilitating Students’ Multiple Intelligences through RME: A Learning Trajectory of Volume and Surface Area Measurement - Ahmad Wachidul Kohar; Achmad Dhany Fachruddin; Soffil Widadah (Jurnal Inovasi Matematika, 2021)
This is a design research which aims to describe the learning trajectory of volume and surface area of rectangular prism by considering the involvement of the multiple intelligences-based activities within the realistic mathematics education (RME) learning activity. A total of 39 students of grade five at an elementary school in Sidoarjo, Indonesia were involved in teaching experiment phase. By collecting data through documentation, interviews, and classroom observations, the Hypothetical Learning Trajectory which was developed in pilot experiment was then revised to get a revised learning trajectory reported in this paper. Such a revised learning trajectory are the learning activities around drawing the nets of cube and cuboids through rolling activity, comparing surface are and volume of two models with different sizes, finding surface area using the constructed nets, building miniature buildings using cube unit model, predicting the number cube units in a box, constructing various models of cuboids to various sizes using particular number of cube units, rearranging a number of cube units arrangements with different layers to get different volume and surface area, and comparing the volumes of two rectangular prism made from the same rectangular model of paper. Lastly, at the ‘formal level’ students developed their informal knowledge into formal concepts of volume and surface area of rectangular prism, which in this case is cuboid and cube.